Peran Pemerintah Daerah untuk Mewujudkan Kota Layak Anak di Indonesia - Darmini Roza; Laurensius Arliman S (Fakultas Hukum Universitas Islam Indonesia, 2018)
The main problems in this research were, first, how is the participation of local governments in realizing children-friendly city/district (KLA) in Indonesia. Second, what are the factors that affect the local governments in realizing children-friendly city/district in Indonesia. This was a normative legal research; legal materials were analyzed using descriptive qualitative approach. The results of the research showed that: first, the forms of participation of the local governments in fulfilling children’s rights so that they deserve to be declared as KLA are: 1) Civil Rights and Freedom; 2) Family and Alternative Nursery; 3) Disability, Basic Health and Welfare; 4) Education, Utilization of Leisure Time and Cultural Activities; and 5) Special Protection. Second, there are several factors that affect how a region becomes KLA: 1) Legislation and policies on the fulfillment of children's rights; 2) Budget for the fulfillment of children's rights; 3) The number of legislations, policies, programs and activities that get input from children forum and other children groups; 4) Availability of KLA-trained human resources who are able to integrate children’s rights into policies, programs and activities; 5) Availability of children’s data by sex, age, and sub-districts; 6) Involvement of community institutions in the fulfillment of children's rights; and 7) Involvement of business in the fulfillment of children’s rights.